2021
DOI: 10.3389/fpubh.2021.671782
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-to-Vigorous Physical Activity Is Associated With Cardiorespiratory Fitness Among Primary Schoolchildren Living in Côte d'Ivoire, South Africa, and Tanzania

Abstract: Background: Physical inactivity and low cardiorespiratory fitness (CRF) are independent cardiovascular risk factors among children, but have rarely been investigated concurrently in sub-Saharan Africa. The purpose of this study was to compare physical activity (PA) and CRF of primary schoolchildren living in Côte d'Ivoire (CI), South Africa (ZA), and Tanzania (TZ), to test sex- and age-related differences, and to examine whether PA and CRF are associated with each other.Methods: Baseline data from an ongoing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 60 publications
(88 reference statements)
3
6
1
Order By: Relevance
“…Moreover, 61.7% of all learners engage in a sedentary lifestyle of which the majority are girls (61.0%). Our findings are supported by those of Gerber et al 12 residence indicated that learners from urban (n = 136; 77.3%) and peri-urban areas (n = 149; 63.4%) had higher levels of sedentary behaviour as compared to those from rural areas (n = 252; 54.9%). This is mainly attributed to the easy access to transport because of the unsafe environment, and the distance between schools and residential areas makes it difficult for these learners to walk to school.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, 61.7% of all learners engage in a sedentary lifestyle of which the majority are girls (61.0%). Our findings are supported by those of Gerber et al 12 residence indicated that learners from urban (n = 136; 77.3%) and peri-urban areas (n = 149; 63.4%) had higher levels of sedentary behaviour as compared to those from rural areas (n = 252; 54.9%). This is mainly attributed to the easy access to transport because of the unsafe environment, and the distance between schools and residential areas makes it difficult for these learners to walk to school.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, generally, the sampled primary school children do not comply with the healthbased guidelines for PA and do not meet the recommended levels of daily PA endorsed by the World Health Organization. 10,17 On the contrary, Gerber et al 12 reported that most primary school children (76.9%) in South Africa met WHO recommendations. In PA participation, we found out that the majority of the learners reported low PA levels (PAQ-C score of 2.33 ± 0.43), especially girls.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…All schools (quintile 3 schools) were located in peri-urban, marginalized communities. Results from this study have been published previously [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. However, the objectives articulated above have yet to be examined, and hence, the findings presented in the current publication are original.…”
Section: Methodsmentioning
confidence: 99%